2007
DOI: 10.1529/biophysj.106.099531
|View full text |Cite
|
Sign up to set email alerts
|

Protein Stability in Ice

Abstract: This study presents an experimental approach, based on the change of Trp fluorescence between native and denatured states of proteins, which permits to monitor unfolding equilibria and the thermodynamic stability (DeltaG degrees ) of these macromolecules in frozen aqueous solutions. The results obtained by guanidinium chloride denaturation of the azurin mutant C112S from Pseudomonas aeruginosa, in the temperature range from -8 to -16 degrees C, demonstrate that the stability of the native fold may be significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 25 publications
5
79
1
Order By: Relevance
“…Freezing introduces complex physical and chemical changes including creation of new ice/solution interfaces, [48][49][50] adsorption to container surfaces, 50 cryoconcentration of the protein and solutes, 51,52 and pH changes due to crystallization of buffer components. 53 These effects are regarded as possible causes of freezing-induced protein denaturation and aggregation.…”
Section: Freezing and Thawingmentioning
confidence: 99%
“…Freezing introduces complex physical and chemical changes including creation of new ice/solution interfaces, [48][49][50] adsorption to container surfaces, 50 cryoconcentration of the protein and solutes, 51,52 and pH changes due to crystallization of buffer components. 53 These effects are regarded as possible causes of freezing-induced protein denaturation and aggregation.…”
Section: Freezing and Thawingmentioning
confidence: 99%
“…Removing solvent, mostly water, is important because a liquid state protein or peptide is unstable to store. It is due to the hydrolysis or oxidation of protein in the presence of water, which results in various kinds of denaturation such as gelation, aggregation and degradation (Kreilgaard et al, 1998;Gabellieri et al, 2003;Gabellieri et al, 2006;Strambini et al, 2007). However, the removal of water may cause structural changes in the secondary and/or tertiary structure of protein.…”
Section: Introductionmentioning
confidence: 99%
“…As evidence to the contrary, i.e., of interaction of non-antifreeze-proteins with ice interface, studies reported in [38,39] are commonly invoked, and discussed below in some detail. Conformational changes of globular proteins were studied by employing the phosphorescence emission of tryptophan (Trp) residues as a monitor of the conformational changes of six proteins in response to variations in conditions of the medium [38].…”
Section: Protein Sorption On Interfacesmentioning
confidence: 99%